2D MODEL OF THE CRUST AND UPPERMOST MANTLE ALONG RIFT PROFILE, SIBERIAN CRATON - Pavlenkova G.A.; Priestley K.; Cipar J. (My University, 2002)
A two-dimensional model of the crust and uppermost mantle for the western Siberian craton and the adjoining areas of the Pur-Gedan basin to the north and Baikal Rift zone to the south is determined from travel time data from recordings of 30 chemical explosions and three nuclear explosions along the RIFT deep seismic sounding profile. This velocity model shows strong lateral variations in the crust and sub-Moho structure both within the craton and between the craton and the surrounding region. The Pur-Gedan basin has a 15-km thick, low-velocity sediment layer overlying a 25-km thick, high-velocity crystalline crustal layer. A paleo-rift zone with a graben-like structure in the basement and a high-velocity crustal intrusion or mantle upward exists beneath the southern part of the Pur-Gedan basin. The sedimentary layer is thin or non-existent and there is a velocity reversal in the upper crust beneath the Yenisey Zone. The Siberian craton has nearly uniform crustal thickness of 40–43 km but the average velocity in the lower crust in the north is higher (6.8–6.9 km/s) than in the south (6.6 km/s). The crust beneath the Baikal Rift zone is 35 km thick and has an average crustal velocity similar to that observed beneath the southern part of craton. The uppermost mantle velocity varies from 8.0 to 8.1 km/s beneath the young West Siberian platform and Baikal Rift zone to 8.1–8.5 km/s beneath the Siberian craton. Anomalous high Pn velocities (8.4–8.5 km/s) are observed beneath the western Tunguss basin in the northern part of the craton and beneath the southern part of the Siberian craton, but lower Pn velocities (8.1 km/s) are observed beneath the Low Angara basin in the central part of the craton. At about 100 km depth beneath the craton, there is a velocity inversion with a strong reflecting interface at its base. Some reflectors are also distinguished within the upper mantle at depth between 230 and 350 km.